Analysis of the implementation of the ISO 14001 environmental management system in a concrete manufacturing plant - Elza Muthia; Tri Joko; Onny Setiani (Malahayati International Journal of Nursing and Health Science, 2025)
Background: One of the main efforts in promoting sustainability is the implementation of ISO 14001, an international standard for Environmental Management Systems (EMS). In addition to helping companies comply with environmental regulations and reduce the risk of legal sanctions, ISO 14001 also contributes to improving operational efficiency, reducing costs, and achieving business sustainability. Effective implementation not only supports environmental preservation but also creates healthier and more productive working conditions. Purpose: To analyze the implementation of the ISO 14001 environmental management system in a concrete production plant. Method: Descriptive observational research with a qualitative approach using a cross-sectional design. This research was conducted at a concrete production company in Demak City, namely PT Varia Usaha Beton Plant Sayung, which has been operating since 1991 and employs 59 workers. The researcher determined the main informant as the subject of this research, namely the manager who is directly responsible for the implementation of ISO 14001 and workers from the quality control section, while for the triangulation informant the researcher chose the Factory Head. ISO 14001 contains 10 clauses, but the researcher only used six clauses with a checklist to assess the implementation of ISO 14001, including organizational context, leadership, planning, support, operations, performance evaluation, and continuous improvement. Results: The implementation of ISO 14001 is in accordance with the standard of 87.2%. Around 71.1% of respondents have a smoking habit which is a major concern in the context of occupational health. This habit can increase the prevalence of health problems such as shortness of breath and flu/prolonged cough observed in some respondents. As many as 20.3% of respondents experienced shortness of breath while working, and 76.2% experienced flu or cough for more than a week. These figures are quite high and may indicate exposure to dust, air pollution, or poor ventilation in the workplace. Most respondents had no history of illness (83.1%), but the high prevalence of respiratory symptoms indicates the need for an environmental evaluation in the workplace. The results of dust measurements also showed that there were areas where the threshold value was exceeded. Conclusion: Although the company has taken positive steps in implementing an environmental management system, controlling dust and enhancing protection for workers remains a critical focus to prevent occupational diseases that are still occurring. Suggestion: To improve the effectiveness of the Environmental Management System (EMS), organizations need to strengthen operational control and communication with external suppliers to ensure that all processes and business partners meet the established environmental standards. In addition, emergency preparedness should be improved through regular evaluation of emergency response procedures, so that responses to critical situations can be faster and more effective.